Tax Digitalization and Tax Service Quality’s Effects on Taxpayer Obligation During the Pandemic Era - Ramadhani, Satriyo; Sitorus, Riris Rotua (Interdisciplinary Social Studies, 2022)
Background: The pandemic, also known as COVID-19, has a significant impact on the global economy and tax system. As a result, taxes will be lower, and national economic growth will be slower, national income will be lower, and spending and financing will be higher. Aim: The author decided to do research into the relationship between digitalization and the quality of taxes, tax incentives, and taxpayer obligations. Method: This research applied quantitative approach and a total of 400 respondents were selected from regular persons who have served as tax commissioners in DKI Jakarta and have used online tax services. Findings: Tax digitalization, the quality of tax services, and tax incentives have all benefited from taxpayer compliance during the COVID-19 pandemic. Throughout the COVID-19 epidemic, tax incentives can help to attenuate, if not strengthen, the influence of tax digitization on taxpayer compliance.